Wyoming bride - Johnston, Joan, 1948- (Johnston, Joan, 1948- Bitter Creek series., 2013)
Newly widowed, pregnant and alone in the Wyoming wilderness, Hannah Wentworth agrees to marry Flint Creed, a bitter man who is in desperate need of a wife, and as the danger of the wild frontier surrounds them, the greatest threat of all are the secrets between them.